MIXED-USE DEVELOPMENTS IN PHOENIX AND TEMPE, ARIZONA: SUSTAINABILITY CONCERNS AND CURRENT TRENDS - Bálint Zoltán TÓTH (Folia Geographica, 2023)
In parallel with the growing concerns of climate change, sustainability, and a perceived lack of urban vibrancy and vitality, an increased number of planning and design movements, policies, and incentives have emerged in the US during the last decades, criticizing urban sprawl and praising the idea of 15-minute, compact cities. However, the tools meant to achieve these, including transport-oriented and mixed-use developments were typically hampered by residential perceptions and demand, especially in the spread, auto-dependent urban regions of the western USA. The aim of the research was to explore current trends in the development of mixed-use projects and the extent to which these processes are stimulated by sustainability concerns in Phoenix and Tempe, Arizona, located in one of the most spread urban regions in the world. Interviews were conducted with planners and city representatives in the Phoenix Metropolitan Area, which are complemented by the review of municipal strategies and zoning ordinances, visualization and analysis of GIS data, and implementation of site visits. The findings show that the strategic aspirations towards mixed-use developments lack environmental considerations due to public perceptions being tied to other issues related to mixed-use developments, which can be traced primarily to Phoenix Downtown. As general difficulties, concerns aggravated by political, administrative, and funding problems. However, decoupled from sustainability, mixed-use developments are likely to proliferate in the Phoenix and Tempe areas due to political will and continuous gentrification processes.